Description of Patient Knowledge About Candesartan After Pio Medicine Through Leaflet Media in Outpatient Depo Of RSUD Moch. Ansari Banjarmasin - M. Reinaldi Pratama; Sri Rahayu; Ananda Mellyani Hidayat (JCPS (Journal of Current Pharmaceutical Sciences), 2019)
The awareness of the Indonesian population to take antihypertensive medication (OAH) is still low, there needs to be more intensive education about the importance of taking medicine so that hypertension can be controlled. The active role of pharmacy technical staff to assist pharmacists is very much needed in providing drug information (PIO) to patients and families of patients. The purpose of this study was to find out how the description of the knowledge of hypertensive patients about candesartan drugs after the provision of drug information through the media leaflets in the Outpatient Depo of the General Hospital Moch. Ansari Saleh Banjarmasin. The researcher took the data using a questionnaire given to hypertensive patients who used candesartan drugs after PIO through leaflets. The results of this study from 32 respondents obtained respondents who have good knowledge, namely 25 respondents (78.125%) and sufficient knowledge that is 7 respondents (21.875%). There were no respondents with a poor level of knowledge about candesartan drug information.